Lời giải:
a.
$=3x^3-6x^2+9x-(3x^3-5x^2+2x)$
$=-x^2+7x=-10^2+7.10=-30$
b.
$=x^3+x^2y-y^3-yx^2=x^3-y^3=20^3-2^3=7992$
c.
\(=[(x+3)+(x-3)]^2=(2x)^2=(-10)^2=100\)
a: Ta có: \(3x\left(x^2-2x+3\right)-\left(3x-2\right)\cdot\left(x^2-x\right)\)
\(=3x^3-6x^2+9x-3x^3+3x+2x^2-2x\)
\(=-4x^2+10x\)
\(=-4\cdot100+10\cdot10\)
=-300
b: Ta có: \(x^2\left(x+y\right)-y\left(x^2+y^2\right)\)
\(=x^3+xy^2-x^2y-y^3\)
\(=\left(x-y\right)\left(x^2+xy+y^2\right)-xy\left(x-y\right)\)
\(=\left(x-y\right)\left(x^2+y^2\right)\)
\(=\left(20-2\right)\left(20^2+2^2\right)\)
\(=18\cdot404=7272\)